Michael of Ephesus. A Commentator of Aristotle and a Thinker - Arabatzis, Georges (Peitho. Examina Antiqua, 2012)
The article examines the state of research on Michael of Ephesus as a probable author of the Commentaries on Metaphysics E–N, mainly the works of Leonardo Tarán and Concetta Luna. In spite of their opposed views (Tarán rejects Michael’s authorship of the commentaries, while Luna supports it), they both agree on the mediocrity of the Byzantine author. The article questions the criteria for this negative appraisal and offers some material for reconsidering Michael of Ephesus’ idea of philosophical culture.